Cinnamon: A Natural Feed Additive for Poultry Health and Production—A Review - Akhtar Ali; Eric N. Ponnampalam; Gamini Pushpakumara; Jeremy J. Cottrell; Hafiz A. R. Suleria; Frank R. Dunshea (Animals, 2021)
The increased bacterial resistance to synthetic antibiotics and consumer awareness about the health and food safety concerns have triggered the ban on the use of antibiotic growth promotors (AGPs) in the poultry industry. This situation encouraged the poultry sector and industry to explore safe alternatives to AGPs and focus on developing more sustainable feed management strategies to improve the intestinal health and growth performance of poultry. Consequently, phytogenic feed additives (PFAs) have emerged as natural alternatives to AGPs and have great potential in the poultry industry. In recent years, cinnamon (one of the most widely used spices) has attracted attention from researchers as a natural product with numerous health benefits for poultry. The essential oils in cinnamon, in particular, are of interest because of their antioxidant, anti-microbial, anti-inflammatory, antifungal, and hypocholesterolaemic effects, in addition to their ability to stimulate digestive enzymes in the gut. This review mainly emphasizes the potential impact of cinnamon as a natural feed additive on overall gut health, nutrient digestibility, blood biochemical profile, gene expression, gut microbiota and immune response.